Bernardino Ramazzini (1633-1714) and his comprehensive lesson in occupational risks prevention, workers health protection and promotion - Franco, Giuliano (Revista Cubana de Salud y Trabajo, 2021)
Academic at the School of Medicine of Modena, Bernardino Ramazzini lived in the second half of the seventeenth century. Although his work is mainly remembered for being the first systematic contribution to the knowledge of occupational diseases, it deserves more detailed and complete consideration. This essay aims at illustrating his visionary engagement in visiting workplaces, identifying health threats, suggesting measures for preventing risks and protecting workers' health. Many aspects of his thinking can be acknowledged: (i) understanding the association between environment and health, (ii) suspecting the environmental origin of every disease, (iii) proposing interventions aiming at risk protection, (iv) providing suitable recommendations for a healthy lifestyle, and (v) suggesting a relevant strategy to fight a devastating rinderpest epidemics occurring at the time.